2020
DOI: 10.1016/j.jpubeco.2020.104271
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on student experiences and expectations: Evidence from a survey

Abstract: Noah Deitrick and Adam Streff provided excellent research assistance. All errors that remain are ours. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
497
11
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(549 citation statements)
references
References 14 publications
28
497
11
13
Order By: Relevance
“…However, improved learning was not reported by any students who had not previously taken online classes (n = 52). These findings are in contrast with those of Aucejo et al [28], who found that the pandemic had diverse impacts on students, with similar shares reporting increased and decreased time spent learning.…”
Section: Studentscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, improved learning was not reported by any students who had not previously taken online classes (n = 52). These findings are in contrast with those of Aucejo et al [28], who found that the pandemic had diverse impacts on students, with similar shares reporting increased and decreased time spent learning.…”
Section: Studentscontrasting
confidence: 99%
“…As a result of universities' response to COVID-19, students have delayed graduation, missed job opportunities, and an estimated 29% expect decreased earnings by the age of 35 [28].…”
Section: Studentsmentioning
confidence: 99%
“…On top of the famed challenging life stage transitioning to adulthood, COVID-19 pandemic has drastically changed lifestyle and educational landscape of students at all levels of education, with unprecedented consequences. For example, various effects have been recorded among undergraduate students at Arizona State University (USA), with systematical differences according to their socioeconomic status and health, resulting in either a decrease or increase of the time spent studying, graduation delay, job losses and job offers acceptance reduction, as well as internship interruptions [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most emphasized thing on the characteristics of online learning is towards student independence and control is with students [20], for that effort related to it is important to do. However, common problems experienced in online learning today are limited infrastructure [1], [2], limited human resource capabilities [20], and low motivation [5], [6], [7], [8].…”
Section: A E-learning During Covid-19 Pandemicmentioning
confidence: 99%
“…The second problem is the decline in students' mental health during the lockdown period which has an impact on the low motivation of students towards the online learning system during Covid-19 pandemic. [5], [6], [7], [8]. However, this pandemic condition cannot be avoided, therefore efforts to increase user acceptance and motivation of online learning are also important [3].…”
Section: Introductionmentioning
confidence: 99%